Assessment of Anthropogenic Impact on Ecosystem Service Safety of Agboyi River in Lagos, Southwestern, Nigeria - Yahaya, Tajudeen Olanrewaju; Salisu, Titilola Fausat; Yunusa, Abdulganiyu; John, Emmanuel; Yusuf, Abdulrahman Bashir; Abdulrazak Karabonde Umar; Abe, Oluwatosin (Tecno Scientifica Publishing, 2023)
The Agboyi River in Lagos, Nigeria provides important ecosystem services; however, anthropogenic activities are polluting the river, necessitating periodic monitoring. This study assessed the heavy metal content (lead, cadmium, chromium, copper, and arsenic) in water samples from the river. Additionally, we evaluated various physicochemical parameters, including pH, total dissolved solids (TDS), conductivity, hardness, magnesium, calcium, chloride, sulfate, and nitrate. The values of each heavy metal were used to calculate human average daily ingestion (ADI), average daily dermal exposure (ADDE), hazard quotient (HQ), and carcinogenic risk (CR). The physicochemical analysis revealed non-permissible levels of TDS, electrical conductivity, alkalinity, hardness, magnesium, calcium, sulfate, nitrate, chloride, and phosphate. The heavy metal analysis showed intolerable levels of lead, arsenic, cadmium, chromium, and copper. The ADIs for the heavy metals were within the recommended dietary intake (RDI), but their ADDEs exceeded the RDI, except for chromium. The HQ and CR for all heavy metals exceeded recommended limits. Seasonal variations were observed in the physicochemical parameters, with TDS, turbidity, acidity, nitrate, and phosphate being higher in the wet season, while other parameters were higher in the dry season. The water poses health hazards to users, indicating the need for river remediation.